Autism spectrum disorder: outcomes in adulthood. Issue 2 (March 2017) - Howlin, Patricia; Magiati, Iliana
Abstract : Purpose of review: Until recently, there has been little systematic study of adult life among individuals with autism spectrum disorder (ASD) but recognition of the high psychological and social costs of ASD has led to an increase in adult-focused research over the past decade. The aim of this review is to summarize recent empirical findings on outcomes for adults with ASD. Recent findings: Most research on adult outcomes in ASD indicates very limited social integration, poor job prospects and high rates of mental health problems. However, studies vary widely in their methodology, choice of measures and selection of participants. Thus, estimates of how many adults have significant social and mental health problems are often conflicting. There is little consistent information on the individual, familial or wider social factors that may facilitate more positive social and psychological outcomes. There is a particular dearth of research on older individuals with ASD. Summary: The very variable findings reported in this review reflect the problems of conducting research into lifetime outcomes for individuals with a condition as heterogeneous as ASD. Much more systematic research is needed to delineate different patterns of development in adulthood and to determine the factors influencing these trajectories.